Reachability Problems Third International Workshop, RP 2009, Palaiseau, France, September 23-25, 2009, Proceedings - Bournez, Olivier; Potapov, Igor (Theoretical Computer Science and General Issues, 2009)
This book constitutes the research papers presented at the 3rd International Workshop, RP 2009 held in Palaiseau, France, September 23-25, 2009. The 20 full papers of this workshop reflect reachability problems that appear in algebraic structures, computational models, hybrid systems and verification. Reachability is a fundamental problem in the context of many models and abstractions which are describing various computational processes. Topics of interest include reachability problems in infinite state systems, rewriting systems, dynamical and hybrid systems, reachability problems in logic and verification, reachability analysis in different computational models, counter, timed, cellular, communicating automata, Petri-Nets, computational aspects of algebraic structures and predictability in iterative maps and new computational paradigms. .